Analyzing the Northern Key Economic Region of Vietnam and Rest of Vietnam Based on Interregional Input - Output Model - Nhung, Nguyễn Hồng; Phong, Nguyễn Việt; Thái, Nguyễn Quang; Trinh, Bùi (International Journal of Economics, Business and Management Studies, 2019)
This study focuses on analyzing the relationship of the Northern Key Economic Region (NKER) and the Rest of Vietnam (ROV) region on the basis of using the Interregional Input – Output table in 2012 and 2016. Some findings show the important effects of the Northern Key Economic Region of Vietnam to Rest of Vietnam region, as well as some policy suggestions on developing key economic regions of Vietnam in the coming time. This study shows that the Northern Key Economic Region is more efficient than the Rest of Vietnam and maintains this trend during 2012 (representing the 2010-2014 period) compared to the year 2016 (representing the 2015-2019 period). The Northern Key Economic Region has effectively used inputs from products in the region, reducing the consumption coefficient of products from the Rest of Vietnam and importing them. This study applied the ideas on internal and external matrix multilpiers in order to analyze the linkages on multilpier effects interregional feedback effects and spillover effects of NKER and ROV of Vietnam based on the Vietnam Input - Output tables, 2012 and 2016.